Can Cervical Ripening at Term Reduce Cesarean Section Rate? A Comparative Study of Cervical Ripening Versus Expectant Management at Term - Baqai, Shehla; Shaheen, Zubaida; Tufail, Shazia; Ghaffar, Sadia; Kanwal, Rehana; Jaffery, Humaira Osman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the obstetrical outcome in cervical ripening versus expectant management at term and evaluate the efficacy of Dinoprostone as a cervical ripening agent in unfavorable cervix.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital Lahore, Pakistan from Jan 2020 to Jun 2021.Methodology: Five hundred pregnant women were recruited through nonprobability consecutive sampling; the women were randomly placed into two groups of 250 patients each. Group-1 received Dinoprostone Vaginal pessary while Group-2 was the control group with no intervention and expectant management. All women were followed till delivery. The mode of delivery in the two groups and the time interval from cervical ripening till delivery was analyzed and compared.Results: Mean age of the patients was 30.43±4.16 years. Comparison of mode of delivery yielded a statistically significant difference with comparatively greater number of vaginal deliveries (86% vs 64%) in the cervical ripening group as compared to the control group. Mean interval from cervical ripening to delivery in Group-1 was 20.75±3.859 hours, minimum interval being 12 hours while the maximum interval was 48 hours. In both the groups, a significantly greater number of primigravidae (96, 33.1%) were found to have undergone LSCS more than the multigravidae (29, 27.6%).Conclusion: Cervical ripening with Dinoprostone at term is an effective, safe and acceptable method in women with unripe cervix. Dinoprostone application resulted in effective cervical ripening, shortened application delivery interval and decreased cesarean delivery rate.